First time compassionate use of laboratory engineered autologous Zurich skin in a massively burned child - Naiem Moiemen; Clemens Schiestl; Fabienne Hartmann-Fritsch; Kathrin Neuhaus; Ernst Reichmann; Arina Löw; Chantal Stenger; Sophie Böttcher-Haberzeth; Martin Meuli (Elsevier, 2021)
Managing major pediatric burns remains a challenge for the entire multidisciplinary team. Limited donor sites make complete early wound closure impossible and the need for temporary cover options and ideally autologous cultured skin increases. We report the case of a 5 year-old child with a 95% total body surface area (TBSA) deep flame burn and the large scale application of a laboratory grown, autologous dermo-epidermal skin analogue, termed Zurich Skin, justified and permitted as compassionate use. In total, 1626 cm2 of Zurich Skin were transplanted onto the patient, relating to approximately 20% of its TBSA. Zurich Skin was easy to handle and apply, showed excellent engraftment rates of 80-90% over dermal substitutes as well as over allodermal remnants, and after a maturation process lead to a soft and solid, close to natural skin coverage. Unfortunately, the child died after a prolonged and intense struggle due to multiple organ failure. This case delivers the clinical proof of principle that Zurich Skin has the potential to help substantially in acute cases with massive skin loss.